Bioinformatics using computational intelligence paradigms - Jain L C; Schweizer P; Seiffert U (Berlin Springer-Verlag, 2004)
Bioinformatics and computational intelligence are undoubtedly remarkably fast growing fields of research and real-world applications with enormous potential for current and future developments. Bioinformatics Using Computational Intelligence Paradigms co
Keywords: Artificial intelligence; Bioinformatics